2017
DOI: 10.1021/acs.energyfuels.7b00869
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salinity on Oil Recovery (the “Dilution Effect”): Experimental and Theoretical Studies of Crude Oil/Brine/Carbonate Surface Restructuring and Associated Physicochemical Interactions

Abstract: The primary aim of this study was to investigate the "dilution effect", where dilution of the ionic concentration of the fluid injected into oil wells has been found to enhance oil recovery. We have measured crude oil/brine/carbonate surface (calcite) interactions using a variety of dynamic techniques including contact angles, surface forces apparatus, atomic force microscopy, interfacial tension, X-ray photoelectron spectroscopy, and other physical and chemical surface characterization techniques. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 38 publications
7
69
0
Order By: Relevance
“…Because reaction Damköhler numbers are very large in reservoir applications, this result confirms our previous order-of-magnitude estimates that rock dissolution occurs at the injection wellbore(Yutkin et al 2018). Consequently, once past the reaction zone, any rock-dissolution-based mechanisms in low salinity waterflood are impossible(Chen et al 2017). From the corresponding concentration histories inFigure 4, rock reaction neither speeds nor slows species transport advance.…”
supporting
confidence: 86%
“…Because reaction Damköhler numbers are very large in reservoir applications, this result confirms our previous order-of-magnitude estimates that rock dissolution occurs at the injection wellbore(Yutkin et al 2018). Consequently, once past the reaction zone, any rock-dissolution-based mechanisms in low salinity waterflood are impossible(Chen et al 2017). From the corresponding concentration histories inFigure 4, rock reaction neither speeds nor slows species transport advance.…”
supporting
confidence: 86%
“…Raising the temperature has been found to be of great benefit for EOR [12,14], while at high temperatures Mg 2+ can even substitute Ca 2+ from the chalk surface [12]. More recently, the injection of low-salinity brine in carbonate reservoirs was reported to enhance oil recovery [14][15][16][18][19][20]. It was further demonstrated that the low-salinity effect results from wettability alteration rather than mineral dissolution [19,21], but the specific mechanism responsible for the wettability alteration remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Any 4 substantial roughening of calcite led to a significant increase of the repulsive mechanical force contribution.Even though the AFM is an extremely powerful tool in force measurements, it usually provides no information about the instantaneous changes in contact surface topography. In this work, we used the Surface Forces Apparatus (SFA), a force measuring technique that enables in situ observations of surface alteration processes by multiple beam interferometry (MBI) 42,[48][49] . We follow how the growth, dissolution and related changes in surface roughness in µm-sized contact areas affect the magnitude and range of forces between dynamic and rough, polycrystalline calcite surfaces.…”
mentioning
confidence: 99%